Grape Composition under Abiotic Constrains: Water Stress and Salinity - Mirás-Avalos, José M.; Intrigliolo, Diego S. (Frontiers in Plant Science, 2017)
Water stress and increasing soil salt concentration represent the most common abiotic constrains that exert a negative impact on Mediterranean vineyards performance. However, several studies have proven that deficit irrigation strategies are able to improve grape composition. In contrast, irrigation with saline waters negatively affected yield and grape composition, although the magnitude of these effects depended on the cultivar, rootstock, phenological stage when water was applied, as well as on the salt concentration in the irrigation water. In this context, agronomic practices that minimize these effects on berry composition and, consequently, on wine quality must be achieved. In this paper, we briefly reviewed the main findings obtained regarding the effects of irrigation strategies, as well as irrigation with saline water, on the berry composition of both red and white cultivars, as well as on the final wine. A meta-analysis was performed using published data for red and white varieties; a general liner model accounting for the effects of cultivar, rootstock and midday stem water potential was able to explain up to 90% of the variability in the dataset, depending on the selected variable. In both red and white cultivars, berry weight, must titratable acidity and pH were fairly well simulated, whereas the goodness-of-fit for wine attributes was better for white cultivars.